How Can Funders Open Up Recognition? (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This ePIC 2025 panel examined funders as often-overlooked stakeholders in advancing open and flexible recognition. Framed by Don Presant and moderated by Patrick Werquin, the discussion drew on the experience of two funding organizations: Canada’s Future Skills Centre and the UK’s UFI VocTech Trust. Together, the panel explored how funders can support innovation in recognition while navigating the tensions between accountability, creativity, equity, and systems change. A central theme was the challenge of funding for innovation without over-prescribing solutions. Tricia Williams described how large volumes of applications often reflect constrained thinking: applicants tend to propose narrow, implementation-ready pilots rather than ambitious redesigns of institutional or ecosystem practice. Josh Smith echoed this, noting that many applicants try to guess what funders want rather than articulating a clear problem and a strong, context-sensitive solution. In both Canada and the UK, this has been intensified by “hype cycles” around AI, with many proposals invoking technology superficially rather than meaningfully. The panel argued that funders need to invest not only in implementation, but also in design. Williams highlighted the importance of supporting structured design processes, technical assistance, theory-of-change development, and experimentation before implementation begins. Smith described similar efforts through design thinking, funded evaluation, and partnership-based models that allow funders to work more collaboratively with trusted organizations on systemic challenges such as digital badging infrastructure, leadership capacity, and adoption barriers. Technology was discussed as necessary but insufficient. Both panelists warned against treating technology as a magic bullet. Evaluations of digital platforms and tools showed that technical solutions often fail when separated from organizational practice, human support, and institutional coordination. For underserved populations in particular, human caseworkers, intermediaries, and relational support remains essential. The panel therefore emphasized a problem-first, solution-second approach, with technology serving broader goals rather than driving them. The conversation also addressed the difficulty of balancing short-term pilots with long-term sustainability. Funders acknowledged structural pressures toward project-based funding, but pointed to loyalty, follow-on support, and venture-style investment as ways to help promising initiatives move beyond proof of concept. Equity was not treated as secondary to efficiency, but as integral to effective funding strategy. Both organizations described equity as embedded across their portfolios, particularly through a focus on learners furthest from traditional provision. The panel concluded by reframing the funder’s role: not as a distant allocator of resources, but as an active, informed partner in ecosystem development. The most productive funding relationships were described as those in which grantees bring deep knowledge of learners and problems, and funders help create the conditions for durable, systemic change. Keywords: innovation and systems change; design grants and partnership funding; equity in skills development; technology enabled recognition This abstract was AI-generated from the original recording of the session and then revised by the editors for accuracy and clarity.